Impact of COVID-19 on mental health of infertile couple: A rapid systematic review - Morvarid Irani; Maryam Hassanzadeh Bashtian; Narges Soltani; Fatemeh Khabiri (Wolters Kluwer Medknow Publications, 2022)
Infertile couples experience a lot of psychological stress due to the inability to achieve the desired social role. Couples who decide to continue assisted reproductive therapy (ART) during the epidemic also experience the psychological impact of the COVID-19 epidemic, which affects their daily lives due to social isolation, quarantine, travel restrictions, and cancellation of treatment. Therefore, the purpose of this study was to assess the mental health of infertile couple pausing or delaying their treatment due to the COVID-19 pandemic. PubMed, Scopus, Cochrane, Embase, Web of Science, ScienceDirect, Google Scholar, Research Gate, and the World Health Organization databases and websites were systematically searched for original studies concerning abortion in the era of COVID-19 pandemic published by August 15, 2021. We used the following keywords: "COVID-19 Corona virus, infertility, reproductive technique, fertilization, assisted reproduction, pregnant termination, psychological, in vitro mental status, depressive symptoms, and anxiety." In sum, after automatically and manually search and excluding duplicates, 269 articles were found. In final, after screening, 18 articles were selected. Most patients experienced negative emotions during the COVID-19 epidemic. When reproductive services were re-established, participants showed higher levels of anxiety and lower quality of life than before quarantine. Women who thought pregnancy was more important than getting COVID-19 had higher levels of anxiety than women who thought otherwise (P < 0.05). The COVID-19 pandemic has negative impacts on the mental health and quality of life of patients seeking fertility services and coping with it requires timely and appropriate psychological intervention, accurate information, and social and organizational support.